Current Status of Buprenorphine/ Naloxone Maintenance Treatment in Istanbul Turkey - Evren, Cüneyt (Addicta: The Turkish Journal on Addictions, 2015)
Although the rate of opioid abuse in Turkey is lower than that in North America and Europe, opioid abuse is an increasing public health problem in Turkey. This is because of both the use of heroin and the increasing number of individuals dependent on prescription opioids. Opioid maintenance treatment (OMT) for opioid dependence is effective in reducing mortality, HIV transmission, crime, and other drug use. Buprenorphine (BUP) maintenance is effective in treating opioid dependence, but problems with the misuse and diversion of BUP might limit its acceptability and dissemination. Abstinence oriented symptomatic treatment was the most commonly offered treatment option in Turkey until the end of 2009. Agonist treatments, including methadone, a single form of buprenorphine or a combined form of buprenorphine and naloxone (BN) were not available. Starting in April 2010, BN was approved for opioid dependence treatment as a detoxification or maintenance treatment by the Turkish Ministry of Health. However, the prescription of BN was restricted to hospitals that included a state-approved specialized clinic for the treatment of substance dependency. In Istanbul, with a population exceeding 13 million inhabitants, only 2 centers provide a BN maintenance treatment program. At the beginning of 2010, the Alcohol and Drug Research Treatment and Training Centre (AMATEM) in Istanbul started providing BN, but only to patients who were hospitalized. At the beginning of 2011, AMATEM published a guideline and extended the implementation of BN OMT to make it available on an outpatient basis. During this time, studies were conducted to evaluate BN OMT.
Keywords: Opioid maintenance treatment; Buprenorphine; Harm reduction; Istanbul; Diversion; Impulsivity